Coaching and Mentoring as Leadership Development Strategies: Roles, Implications, and Organizational Outcomes - Jackson Owoicho Ameh; Edwinah Amah (Pinisi Journal of Social Science, 2025)
Leadership development has emerged as a critical organizational strategy for enhancing performance, fostering innovation, and ensuring long-term sustainability in an increasingly complex global business environment. Among the most prominent approaches to developing leadership capabilities are coaching and mentoring, which facilitate learning, reflection, and behavioral change. This paper critically examines the roles of coaching and mentorship in leadership development through a comprehensive review of theoretical and empirical literature. The study explores the conceptual foundations, mechanisms, and outcomes associated with these developmental interventions while highlighting the consequences of inadequate leadership development in organizations. Key findings suggest that coaching and mentoring, though distinct in their approaches, offer complementary benefits: coaching enhances performance through goal-oriented feedback and self-reflection, while mentoring provides career guidance, psychosocial support, and long-term developmental relationships. The paper discusses the theoretical underpinnings, including experiential learning theory, self-determination theory, and social learning theory, which explain the effectiveness of these interventions. Additionally, the study examines challenges in implementation, practical implications for organizations, and recommendations for integrating coaching and mentoring into comprehensive leadership development frameworks. The paper concludes by emphasizing that organizations seeking sustainable competitive advantage must institutionalize coaching and mentoring as strategic leadership development interventions.